What politics? : youth and political engagement in Africa - Oinas, Elina, 1968-; Onodera, Henri; Suurpää, Leena (Youth in a globalizing world, 2018)
What Politics? Youth and Political Engagement in Africa examines the diverse experiences of being young in today's Africa. It offers new perspectives to the roles and positions young people take to change their life conditions both within and beyond the formal political structures and institutions. The contributors represent several social science disciplines, and provide well-grounded qualitative analyses of young people's everyday engagements by critically examining dominant discourses of youth, politics and ideology. Despite focusing on Africa, the book is a collective effort to better understand what it is like to be young today, and what the making of tomorrow's yesterday means for them in personal and political terms. Contributors are: Ehaab Abdou, Abebaw Yirga Adamu, Henni Alava, Päivi Armila, Randi Rønning Balsvik, Jesper Bjarnesen, Þóra Björnsdóttir, Jónína Einarsdóttir, Tilo Grätz, Nanna Jordt Jørgensen, Marko Kananen, Sofia Laine, Naydene de Lange, Afifa Ltifi, Ivo Mhike, Claudia Mitchell, Relebohile Moletsane, Danai S. Mupotsa, Elina Oinas, Henri Onodera, Eija Ranta, Mounir Saidani, Mariko Sato, Loubna H. Skalli, Tiina Sotkasiira, Abdoulaye Sounaye, Leena Suurpää, and Mulumebet Zenebe.